Wage and salary administration - Miranda, Gregorio S.; Miranda-Gow, Carmelita (Mandaluyong City, Philippines : National Book Store, 1999)
The compensation given to salesmen in the field generally consists of regular salaries plus bonus.
1. Introduction -- 2. Wages and their significance -- 3. Theories of Wages -- 4. Incentive schemes -- 5. Management Incentives -- 6. Significant factors affecting compensation -- 7. Wage supplements -- 8. Merit Rating -- 9. Job description and Job Analysis -- 10. Job evaluation -- 11. Wage Salary surveys -- 12. Wage structure -- 13. Important laws and regulations on wages -- 14. Communication compensation package and benefits -- 15. Pay and performance -- 16. Performance Appraisal -- 17. Salesmen's compensation -- 18. Executive compensation.
Includes bibliographical references.
Keywords: WAGES